1987
DOI: 10.1115/1.3242628
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Fluid Forces on Whirling Centrifugal Impeller (2nd Report: Experiment in Vaneless Diffuser)

Abstract: Fluid forces acting on a rotating centrifugal impeller in whirling motion are studied experimentally. A two-dimensional impeller installed in a parallel walled vaneless diffuser was forced on a circular orbital motion at various positive and negative whirl speeds. The measurements show that the fluid forces exert a damping effect on the rotor at most operating conditions, but excite positive whirl when the impeller operates at a partial discharge and rotates at speeds more than twice the whirl speed. The test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…This is demonstrated in Eq. (2). In experiments or field measurements, it is well observed that higher harmonic components are more dominant than ZrN or ZgN components (10) .…”
Section: Discussion On Frequency Componentsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is demonstrated in Eq. (2). In experiments or field measurements, it is well observed that higher harmonic components are more dominant than ZrN or ZgN components (10) .…”
Section: Discussion On Frequency Componentsmentioning
confidence: 98%
“…Kanki et al (1) measured the fluid forces in various operating conditions. Ohashi et al (2), (3) investigated experimentally the destabilizing fluid forces to the rotor by whirling the impeller with a DC motor and measuring the reaction forces for various ratios of whirling to rotating. They concluded that the fluid forces of a free impeller basically had a stabilizing effect, but that in the case of a vaned diffuser, the interaction forces might be destabilizing for a small ratio of whirling to rotating.…”
Section: Introductionmentioning
confidence: 99%
“…was indicated by Ohashi (1984), Grant et al (1993), and Muszynska (1995). Within the range ofrotative speeds limited to the first lateral mode, the isotropic rotor model (1) is adequate for the case of the rotor/ bearing system (with fluid whirl and whip tendencies), rotor/seal systems (with seal fluid whip tendency), fluid handling machines with blade-tip or rotor/stator periphery interactions (with fluid whip tendencies), and rotors with press fit rotating elements, exhibiting high internal/structural friction (with internal friction whip tendencies; A 1, Mr= 0).…”
Section: Rotor/fluid Environment Modelmentioning
confidence: 99%
“…b 2 outlet blade height of the impeller C dimensionless direct damping c dimensionless cross-coupled damping F n normal rotordynamic force f n dimensionless normal rotordynamic force F t tangential rotordynamic force f t dimensionless tangential rotordynamic force K dimensionless direct sti¨ness k dimensionless cross-coupled sti¨ness M dimensionless direct added mass m dimensionless cross-coupled added mass N = Ÿ/(2π) rotational frequency of the shaft Q volumetric §ow rate Q n reference volumetric §ow rate R 2 outlet radius of the impeller t tip clearance between the impeller and the casing ε dynamic eccentricity of the shaft ρ density ā head coe©cient ā dif di¨user head coe©cient ā imp impeller head coe©cient ā n reference head coe©cient ā pump pump head coe©cient Ÿ angular velocity of the shaft ω angular velocity of the whirling motion…”
Section: Nomenclaturementioning
confidence: 99%
“…The rotordynamic forces acting on impellers have been studied since the development of the high-pressure fuel turbopump of the Space Shuttle Main Engine (SSME) [1]. The rotordynamic forces acting on ¤closed¥ impellers have been widely reported, and it is well known that they encourage instability in the low §ow rate region [2]. On the other hand, there have been few reports on the rotordynamic forces acting in ¤open¥ impellers.…”
Section: Introductionmentioning
confidence: 99%